The Causal Relationship between Angina Pectoris and Gout Based on Two Sample Mendelian Randomization - Jian Xiong; Yuxin Sun; Hui Huang; Yu Liu; Fayang Ling; Yin Wei; Qianhua Zheng; Wenchuan Qi; Fanrong Liang (Pain Research and Management)
Purpose. Two-sample Mendelian randomization (MR) was conducted to assess the causal relationship between angina pectoris and gout. Material and Methods. Based on genome-wide association studies, single nucleotide polymorphisms (SNPs) that were closely associated with gout were selected from the UK Biobank–Neale Lab (ukb-a-107) as genetic instrumental variables. Considering that gout is characterized by elevated blood uric acid levels, SNPs related to blood uric acid levels were screened from BioBank Japan (bbj-a-57) as auxiliary gene instrumental variables. SNPs closely associated with angina pectoris onset were screened from the FINN dataset (finn-b-I9_ANGINA) as outcome variables. Two-sample MR was conducted, with inverse variance weighting (IVW) of the random effects model as the primary result, along with the weighted median method (WME) and the MR-Egger regression method. To further confirm the causal relationship between angina and gout incidence, a meta-analysis was conducted on the IVW results of the ukb-a-107 and bbj-a-57. Results. The odds ratios and 95% confidence intervals of the IVW, WME, and MR-Egger results of ukb-a-107 were (OR = 33.72; 95% CI: 2.07∼550.38), (OR = 57.94; 95% CI: 2.75∼1219.82), and (OR = 96.38; 95% CI: 0.6∼15556.93), respectively. The P values of IVW and WME were 0.014 and 0.014 (both <0.05), respectively, indicating that the development of angina pectoris was significantly associated with the incidence of gout. The odds ratios and 95% confidence intervals of the IVW, WME, and MR-Egger about bbj-a-57 were (OR = 1.20; 95% CI: 1.07∼1.34), (OR = 1.19; 95% CI: 1.02∼1.38), and (OR = 1.30; 95% CI; 1.06∼1.60), respectively. The P values of IVW, WME and MR-Egger were 0.001, 0.027 and 0.017 (all <0.05), respectively, indicating a significant correlation between angina and blood uric acid levels. Scatter plots of ukb-a-107 and bbj-a-57 showed that the causal association estimates of the IVW, MR-Egger, and weighted median methods were similar and that the MR results were accurate. Funnel plots and the MR-Egger intercept of ukb-a-107 and bbj-a-57 showed the absence of horizontal pleiotropy. The leave-out sensitivity analysis results of ukb-a-107 and bbj-a-57 are stable. The meta-analysis of IVW results for ukb-a-107 and bbj-a-57 showed (OR = 1.20; 95% CI: 1.07–1.34, P=0.02), confirming that gout characterized by high blood uric acid levels significantly increases the risk of angina attacks. Conclusions. This MR study found a clear causal relationship between angina pectoris and gout, which increases the risk of angina pectoris.